AB0091 Synovial Fluid Hyaluronan Regulates Multipotiental Stromal Cell Attachment to Cartilage a Novel Mechanism Contributing to Knee Joint Distraction Repair in Osteoarthritis. (9th June 2015) - Baboolal, T.; Mastbergen, S.; Calder, S.; Lafeber, F.; Jones, E.; McGonagle, D.
Abstract : Background: Knee joint distraction (KJD) is a novel, but poorly understood, treatment for osteoarthritis (OA) associated with remarkable "spontaneous" cartilage repair in which resident synovial fluid (SF) multipotential stromal cells (MSCs) may play a role. We hypotheses SF hyaluronic acid (HA) may inhibit the initial interaction between MSCs and cartilage, a key first step to integration, and that KJD environment may favour MSC/cartilage interactions. Methods: Human cartilage was used in an in vitro model with dual-labelled SF-MSC, OA and rheumatoid arthritic (RA) SF. SF was digested with hyaluronidase (Hyase) and its effect on adhesion observed using confocal microscopy. Magnetic resonance imaging (MRI) and confocal microscopy were used to image autologous dual-labelled MSCs in an in vivo canine model of KJD. SF-HA was investigated using gel electrophoresis and densitometry. Results: Hyase treatment of OA-SF only, significantly increased MSC/cartilage adhesion (3.7 fold, p<0.05). There was a clear difference in the ability of Hayse to increase adhesion in OA compared to RA-SF (p<0.001). We attribute this difference to the formation of a HA-coat which was ∼50% larger in OA than RA-SF. OA-SF contained more >9MDa HA and this correlated with increases in adhesion (r=0.880). I n vivo, MSC adhesion to cartilage was also dependent on HA MW. Conclusions: These findings highlight an as yet unappreciated role of SF-HA and provide proof of concept that endogenous SF-MSCs are capable of adhering to cartilage in a favourable biochemical and biomechanical environment in OA distracted joints, offering novel one-stage strategies towards joint repair in OA. Disclosure of Interest: None declared